1998
DOI: 10.1073/pnas.95.22.12983
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 is associated with the centrosome during mitosis

Abstract: Centrosomes and their associated microtubules direct events during mitosis and control the organization of animal cell structures and movement during interphase. The centrosome replicates during the cell cycle, directs the assembly of bipolar mitotic spindles, and plays an important role in maintaining the fidelity of cell division. Recently, tumor suppressors such as p53 and retinoblastoma protein pRB have been localized to the centrosome in a cell cycledependent manner. Immunof luorescence microscopy and ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
199
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(207 citation statements)
references
References 40 publications
6
199
0
2
Order By: Relevance
“…These Brca1-defective MEFs showed centrosome amplification with multiple functional centrosomes, which led to unequal chromosome segregation and aneuploidy (Xu et al, 1999b). Consistent with this finding, an earlier study had shown that BRCA1 localizes to the centrosome during mitosis and associates with g-tubulin, a centrosomal protein necessary for the nucleation of microtubules (Hsu and White, 1998;Hsu et al, 2001). These studies suggest a role for BRCA1 in the regulation of centrosome duplication as a component of its function in maintaining genomic integrity.…”
Section: Functional Activities Of Brca1 Cell Cycle Regulation and Gromentioning
confidence: 57%
“…These Brca1-defective MEFs showed centrosome amplification with multiple functional centrosomes, which led to unequal chromosome segregation and aneuploidy (Xu et al, 1999b). Consistent with this finding, an earlier study had shown that BRCA1 localizes to the centrosome during mitosis and associates with g-tubulin, a centrosomal protein necessary for the nucleation of microtubules (Hsu and White, 1998;Hsu et al, 2001). These studies suggest a role for BRCA1 in the regulation of centrosome duplication as a component of its function in maintaining genomic integrity.…”
Section: Functional Activities Of Brca1 Cell Cycle Regulation and Gromentioning
confidence: 57%
“…The most prominent example is the best-characterized breast cancer susceptibility gene BRCA1 11,22 that is linked to the development of breast and ovarian cancers. Importantly, recent genetic studies indicated PIBF among the candidate genes for breast cancer predisposition and cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…11 Exponentially grown HEK 293 cells were incubated with culture medium containing 0.6 g/ml nocodazole and 1 g/ml cytochalasin D for 1 hr at 37°C, to depolymerize microtubule filaments and actin, respectively. The cells were harvested and resuspended in 1ml lysis buffer (1 mM HEPES pHϭ7.2, 0.5% NP-40, 0.5 mM MgCl 2 , 0.1% 2-mercaptoethanol, 1 mM phenylmethylsulfonyl fluoride and Complete™ EDTA free tablets).…”
Section: Centrosome Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumour suppressor proteins including BRCA1 and p53 have also been found to co-localize with centrosomes in mitosis, although how these proteins participate in centrosome regulation it is not known. It is also unknown if they impact on centrosome stability in the context of mitotic DNA damage (Hsu and White, 1998;Kais and Parvin, 2008;Shinmura et al, 2007;Fukasawa, 2007).…”
Section: Growing Evidence Of Centrosomal Checkpoints Responding To Dnmentioning
confidence: 99%